The Effect of Four Hours of Continuous Personal Computer (PC) Gaming on the Development of Dry Eye Symptoms in College Students - Liu D; Cook III BL; Farris EP (Clinical Ophthalmology)
Derrick Liu,1 Bernard L Cook III,2 Edmund P Farris3 1Frank H. Netter MD School of Medicine, Quinnipiac University, North Haven, CT, USA; 2Department of Immunology, UConn Health, Farmington, CT, USA; 3Department of Surgery, Division of Ophthalmology, UConn Health, Farmington, CT, USACorrespondence: Edmund P Farris, UConn Health, 263 Farmington Ave, Farmington, CT, USA, Tel +1 860 679 3389, Email efarris@uchc.eduPurpose: The purpose of this study was to evaluate if a short period of playing video games on a personal computer (PC) causes changes in measurements of dry eye disease (DED).Patients and Methods: We recruited 41 Quinnipiac University students (ages 18– 23 years, mean age 19.66± 1.09 years; 9 females, 32 males), with eligibility criteria being 18+ years old, identifying as “gamers” without previous history of eye surgery, steroid use, autoimmune disorders, or history of or previous treatment for dry eye. Each student was administered DED-related assessments before/after four hours of continuous PC gaming: 1) Standardized Patient Evaluation of Eye Dryness (SPEED) and Ocular Surface Disease Index (OSDI) questionnaires, 2) Snellen visual acuity test, 3) tear osmolarity point-of-care assay, 4) matrix metalloproteinase-9 (MMP-9) inflammation point-of-care assay, and 5) an unanesthetized Schirmer test of tear production. Students were limited to 500 cc of water during the four hour period.Results: Following gaming, the mean SPEED scores increased significantly (p< 0.001, Wilcoxon signed-rank test), as did the frequency and severity of soreness/irritation and eye fatigue. Tear osmolarity decreased and tear production increased in the right eye. Other metrics (OSDI, Snellen, and MMP-9) did not change significantly.Conclusion: As little as four hours of continuous PC gaming with limited hydration results in an increase in self-reported measures of DED symptoms. These prospective findings corroborate the epidemiological link between gaming and DED symptoms and highlight the need for long-term studies.Keywords: dry eye disease, screen use, matrix metalloproteinase-9, tear osmolarity